(untitled) (American Journal of Multidisciplinary Research and Innovation, 2023)
This study aimed to investigate the emotional experiences of 11th-grade students to enhance language learning. Language learning is a complex and demanding process, and emotions can play a critical role in shaping students’ learning experiences. Therefore, the study adopted a qualitative approach and a Grounded Theory research design to examine the impact of emotions on language learning. Data were collected from ten 11th-grade students through interviews and journals. The findings revealed that emotional experiences significantly influenced the behavior of students during classroom instruction. Students’ motivation was significantly impacted by their emotions, as positive and negative emotions could either activate or deactivate their motivational behavior. Furthermore, the study found that experiencing positive and negative emotions could benefit students as it helped them develop emotional control and improve their language learning. Students who were able to regulate their emotions were better able to manage stress, remain focused, and perform better in their language learning tasks. The study highlighted the importance of understanding emotions in language learning and emphasized the role of epistemic emotions, which refer to emotions that arise during the learning process. By understanding how emotions impact language learning, educators can develop more effective teaching strategies that account for the emotional needs of their students.